Find and explain the error in the student’s work/answers below.
Solve: m² + m – 6 = 0
m² – 2m + 3m – 6 = 0
m(m – 2) + 3(m – 2) = 0
(m – 2)(m + 3) = 0
m – 2 = 0 or m + 3 = 0
m = –2 or m = 3
3 answers
The error is in line 2 where the student incorrectly rewrites the equation. The correct way to rewrite the equation would be: m² + m – 6 = 0, which is the original equation given. The student should not have added 3m and then subtracted 2m to the equation. This mistake leads to an incorrect factorization in line 3 and ultimately incorrect solutions in the final step.
m – 2 = 0 or m + 3 = 0
********** m = –2 or m = 3 *********
NO
m = +2 or m = -3
=========================
check
==========================
m² + m – 6 = 0
if m = -2
4 +2- 6 = 0 yes
if m = -3
9 - 3 - 6 = 0 yes
********** m = –2 or m = 3 *********
NO
m = +2 or m = -3
=========================
check
==========================
m² + m – 6 = 0
if m = -2
4 +2- 6 = 0 yes
if m = -3
9 - 3 - 6 = 0 yes
The revised answer with the correct solutions (m = 2 or m = -3) and correct check is correct.